Introductory econometrics for finance / Chris Brooks. - Brooks, Chris, 1971- (Cambridge University Press, 2019)
A complete resource for finance students, this textbook presents the most common empirical approaches in finance in a comprehensive and well-illustrated manner that shows how econometrics is used in practice, and includes detailed case studies to explain how the techniques are used in relevant financial contexts.